THE INFLUENCE OF CORPORATE SOCIAL RESPONSIBILITY (CSR) ACTIVITIES ON BUILDING CORPORATE REPUTATION - Esen, Emel (EMERALD GROUP PUBLISHING LTD, 2013)
Purpose - In business environment, corporate social responsibility (CSR) is becoming increasingly an important issue for every stakeholder. Organizations are being reputable through CSR activities. The aim of this chapter is to examine the relationship between CSR and corporate reputation, and determine the role of CSR activities in corporate reputation building process. Design/methodology/approach - An extensive literature research is conducted in order to develop the theoretical framework that supports the positive role of CSR activities on corporate reputation. Findings - As CSR activities affect the consequences that have a positive impact on corporate reputation, findings show that CSR enables firms to improve reputation with a broad range of stakeholders including employees (internal customers), customers (external customers), suppliers, competitors, bankers, and investors. Research limitations/Implications - However this research is a theoretical study, for further studies an empirical research model may be developed for investigating the relationship between CSR and corporate reputation. These dimensions should be measured and the hypothesis about the positive relationship between CSR and corporate reputation may be statistically tested. Practical implications - This theoretical study may be useful for the board of directors and managers since they should become aware of the importance of one of the growing areas of corporate reputation and CSR. They are also increasingly being encouraged to engage CSR activities into their organization's vision, identity, brand, and reputation. Based on societal expectations of stakeholders, organizations should develop and improve their CSR programs and reflect these developments to their reputation mechanisms. Originality/Value of the paper - This study is valuable to understand the corporate reputation practices that enhance and demonstrate the value of reputable organizations. It is also attractive to compare other dimensions of corporate reputation such as emotional appeal, workplace environment, and corporate reputation with CSR.
Keywords: Corporate social responsibility; corporate reputation; IMPACT; PERFORMANCE; MANAGEMENT; IDENTITY; STAKEHOLDER; LEADERSHIP; COMPANIES; CONSUMERS; STRATEGY; DRIVERS; Environmental Sciences & Ecology; Business & Economics